Drylot receiving program vs pasture conditioning with Micotil® metaphylaxis for grazing stocker calves - Paisley, S.I.; Falkner, Thomas R.; Brazle, F.K.; Stokka, Gerald L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three stocker cattle field studies were conducted comparing a traditional 4- to 5-week drylot receiving program with injectable antibiotics administered on a pull-and-treat basis versus a pasture-based conditioning program using an initial metaphylaxis with Micotil® followed by immediately placing cattle on grass. Although daily gains were similar (P=.80) for both receiving programs during the first 28 days, pasture conditioning reduced the number of cattle treated and increased (P<.01) daily gains during the subsequent grazing phase.
Keywords: Beef; Stockers; Receiving; Metaphylaxis; Micotil®